Strategic Environmental Assessment in China : Motivations, Politics, and Effectiveness - Zhu, D.; Ru, J. (2012)
This paper examines how strategic environmental assessment has been practiced at the national level in China through 2005 and why it has been practiced in the manner observed. Based on literature reviews and interviews carried out in 2005 and 2006, we find that bureaucratic politics between environmental and nonenvironmental ministries has limited the legislation and implementation of strategic environmental assessment to environmental assessment (EA) for a set of government plans defined in the 2003 Environmental Impact Assessment Law. Interviewees from environmental and nonenvironmental ministries and key research institutes have reported that few planning EAs have been performed at the sectoral level. Nonenvironmental ministries have either evaded the 2003 Environmental Impact Assessment Law and have not undertaken required planning EA or have organized planning EA on their own without participation by the State Environmental Protection Administration. The rising tension between the environmental and nonenvironmental ministries has limited the role of planning EA as a participatory decision-making tool. In addition to bureaucratic politics, we find that weak public participation and underemphasis on social analysis in planning EA may have further compromised the utility of planning EA.